Determination of Interfacial Boundary Motion Law in Problems Modeling Phase Transformation Kinetics - V. V. Shevelyov; J. L. Lokshin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
An analytical method for solution of multidimensional problems of heat conductivity with phase transformations which is based on integral equation method has been developed. The method makes it possible to determine interfacial boundary motion law excluding determination of temperature field and it also permits to investigate stability of its shape. The paper reveals that the proposed method is rather efficient in the case when heat transfer takes place in one phase.